POLYSEMY IN GREEK-POLISH AND POLISH-GREEK LEGAL TRANSLATION - GORTYCH-MICHALAK, Karolina (Comparative Legilinguistics, 2013)
Polysemy is a relatively important problem in translation and it requires a translation solution which is adequate to the context. The phenomenon of polysemy seems to be slightly difficult to be defined precisely in linguistics as lingusts analyze polysemy in reference with homonymy. Even if legal language aims at expressing accurately meanings, there are many examples of polysemous terms in statutory instruments including constitutions or statutes which are produced by a virtual author – the legislator. The purpose of the paper is to provide methodological means for finding and to applying adequate translational strategies of dealing with polysemous terms occurring in Greek and Polish legal languages. Some legal terms (words and phrases) derived from the morpheme «πολιτ» [polit] of constitutional, administrative and civil Greek and Polish legal language are investigated. The author of the paper emphasises the connection between the terms and the context in which they occur and points out that context analysis is the only way to find successful translational equivalents meeting the requirements of the pragmatic methodology of legal translation. The research might be prolegomena to further lexicographic studies of the so-called lesser spoken languages including for example Greek and Polish languages. The obtained results of the research might be used in translation studies and practice, language teaching and comparative law.